The Emotional Oversharing in The Quality of Student Friendships In The City of Cirebon - Farida Nurfalah; Syaifah Nazlah (CV. Media Digital Publikasi Indonesia, 2026)
Emotional oversharing is the act of sharing personal information or emotions excessively with others. This study aims to analyze the phenomenon of emotional oversharing among students in Cirebon City and its impact on the quality of friendships. Emotional oversharing refers to the act of sharing personal information or emotions excessively, which can affect the dynamics of interpersonal relationships. The author chose this research topic due to the prevalence of oversharing among university students, particularly in the context of friendship, which often affects the quality of friendships. The research method used was a qualitative approach with a phenomenological design. Data were collected through in-depth interviews with three student informants who had experienced oversharing in their friendships. The results of the study show that psychological factors such as the need for validation, situational factors such as a social environment that supports openness, and relational factors such as the level of familiarity, also influence oversharing. Although oversharing can deepen intimacy in relationships that have been built on trust, the negative impacts are more dominant, such as a decline in the quality of friendships, loss of trust, and the emergence of interpersonal conflicts. These findings emphasize the importance of privacy management in friendship communication, as explained by the Communication Privacy Management (CPM) theory, which highlights the importance of awareness in setting boundaries for personal communication. Overall, this study adds to the understanding of the dynamics of interpersonal communication in the context of friendships among students in Cirebon City.